Slavs to Slavs in Mission Identity of Czech Missionaries in Former Yugoslavia Countries. - Symon, David (Regnum Books International, 2023)
Many would agree that the issue of identity is pertinent for mission. This book explores the case study of Czechs in former Yugoslavia countries with focus on national identity of the missionaries. It aims to help mission practitioners to understand what to beware of and what to benefit from. It provides a fresh insight into mission dynamics in Central and Eastern Europe, yet with its aim on identity negotiation of missionaries could relate to other contexts as well.